2018
DOI: 10.1089/humc.2017.231
|View full text |Cite
|
Sign up to set email alerts
|

AAVrh.10-Mediated APOE2 Central Nervous System Gene Therapy for APOE4-Associated Alzheimer's Disease

Abstract: Alzheimer's disease (AD) is a progressive degenerative neurological disorder affecting nearly one in nine elderly people in the United States. Population studies have shown that an inheritance of the apolipoprotein E (APOE) variant APOE4 allele increases the risk of developing AD, whereas APOE2 homozygotes are protected from late-onset AD. It was hypothesized that expression of the "protective" APOE2 variant by genetic modification of the central nervous system (CNS) of APOE4 homozygotes could reverse or preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(70 citation statements)
references
References 99 publications
1
69
0
Order By: Relevance
“…Intrathecal delivery, direct spinal cord, and brain injections have all demonstrated safety. Presently, there are several viral-mediated gene-therapy clinical trials for neurodegenerative diseases (3), and recent intracisternal AAV delivery in nonhuman primates demonstrated wide transgene expression (35). In December 2017, the Food and Drug Administration approved the first-ever AAV-mediated gene therapy for retinal dystrophy, demonstrating a monumental shift in CNS therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Intrathecal delivery, direct spinal cord, and brain injections have all demonstrated safety. Presently, there are several viral-mediated gene-therapy clinical trials for neurodegenerative diseases (3), and recent intracisternal AAV delivery in nonhuman primates demonstrated wide transgene expression (35). In December 2017, the Food and Drug Administration approved the first-ever AAV-mediated gene therapy for retinal dystrophy, demonstrating a monumental shift in CNS therapies.…”
Section: Discussionmentioning
confidence: 99%
“…This study also showed that gene delivery of APOE2 was most effective before the onset of amyloid burden, suggesting that in order to be a successful therapy the AAV would need to be injected much before the onset of symptoms in patients which poses its own challenges. Further translational studies on non-human primates revealed that intra-cisternal delivery of AAV-APOE2 led to widespread expression in the CNS which established a safe procedure for CNS delivery of biologics [166]. Because of the inherent risk in any surgical procedure inside the CNS, whether such AAV-APOE2 biologics can be directly delivered into the AD-affected areas of the human CNS needs to be cautiously determined.…”
Section: Aav-apoe2 Biologic Therapymentioning
confidence: 99%
“…AAVrh.10CisTau coding for the anti-Tau monoclonal Cis-Tau 33,59 ; and AAVrh.10Null used as a control, identical to the other vectors but with no gene coding sequence. 41 PHF1 hybridoma cell cDNA (gift from Peter Davies, Albert Einstein College of Medicine) was amplified and synthesized in two independent reactions using primer annealing conserved regions of the constant heavy and light chains. The cDNA containing the mouse heavy chain sequence from IgG1 and the mouse Kappa light chain sequence was amplified using nested primers, cloned into a TOPO vector (Thermo Fisher Scientific, Inc., Carlsbad, CA) and sequenced.…”
Section: Aavrh10 Vectorsmentioning
confidence: 99%
“…All vectors were produced using 293T cells as described previously. [40][41][42][43]60 Briefly, the expression plasmid and the AAVrh.10 packaging-Ad helper hybrid plasmid pPAK-MArh.10 were cotransfected into 293T cells using the PEI transfection reagent (Polysciences, Warrington, PA). At 72 h post-transfection, cells were harvested and lysate prepared using five cycles of freeze/thaw.…”
Section: Aavrh10 Vectorsmentioning
confidence: 99%
See 1 more Smart Citation